2018
DOI: 10.2147/ppa.s165203
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in type 2 diabetes mellitus patients with different risk for obstructive sleep apnea

Abstract: PurposeOur study primarily aimed to investigate health-related quality of life (HRQoL) in type 2 diabetes mellitus (T2DM) patients with different risk for obstructive sleep apnea (OSA).Patients and methodsThis cross-sectional, questionnaire-based study included 466 adult patients with T2DM on regular visit to Center for Diabetes of University Hospital of Split from April to September 2017. All subjects underwent detailed anamnestical evaluation and physical examination with anthropometric measurements. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The relationship between diabetes and HRQoL is complex and can be affected by various factors in different contexts. Under this study, multivariate regression model confirmed that age was statistically significantly associated to both physical and mental component of HRQoL, which is consistent with previous studies ( Gabric et al, 2018 ; Wexler et al, 2006 ). Age is the strongest predictor among demographic, lifestyle, and clinical factors ( p < 0.0001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between diabetes and HRQoL is complex and can be affected by various factors in different contexts. Under this study, multivariate regression model confirmed that age was statistically significantly associated to both physical and mental component of HRQoL, which is consistent with previous studies ( Gabric et al, 2018 ; Wexler et al, 2006 ). Age is the strongest predictor among demographic, lifestyle, and clinical factors ( p < 0.0001).…”
Section: Discussionsupporting
confidence: 92%
“…Age is the strongest predictor among demographic, lifestyle, and clinical factors ( p < 0.0001). Similar findings have been reported in both European and Asian studies with inverse correlation of HRQoL and age ( Gabric et al, 2018 ; Wang and Yeh, 2013 ). In the fact that elderly people usually have more than one chronic conditions, which means that they might have cognitive complications and have to take multiple medications, which is one of many factors that impacts their physical and mental health ( Brown et al, 2004 ; Nguyen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…A prospective population-based study did show that people with type 2 diabetes and OSA have a higher risk of cardiovascular mortality (HR 2.37 [95% CI 1.16, 4.82]), compared with people with only type 2 diabetes or only OSA [ 22 ]. Finally, in addition to poorer health outcomes, OSA affects QoL in people with type 2 diabetes; those with OSA score lower in all domains of QoL questionnaires, compared with people with type 2 diabetes only [ 23 ].…”
Section: Prevalence and Health Outcomes Of Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
“…30 It has also been shown in a study that the association of T2DM and OSA casts a toll on the health-related quality of life as assessed by the STOP questionnaire with the correlation being statistically significant. 31 Thus the confederated effects of these two entities are elephantine.…”
Section: Obstructive Sleep Apnea and Diabetes Mellitus: The Effects Of Their Coexistencementioning
confidence: 99%